HIV/AIDS EPIDEMICAL ANALYSIS AND MODELLING THE IMPACT OF PUBLIC HEALTH EDUCATION CAMPAIGN ON THE TRANSMISSION DYNAMICS OF HIV/AIDS - Nyaboe, Moffat C.; Sigey, Johana K.; Giterere, Kangethe (Machakos University, 2018)
The most important factor in the management and control of an infectious disease is the understanding of the dynamics of the disease in any given population. We have proposed and analyzed a nonlinear mathematical model for the spread of HIV/AIDS in a population with variable size structure. The model was developed by adopting the compartmental modeling approach where the population was partitioned into; Susceptible, Infected and Aids subpopulations. A threshold parameter is found that completely determines the stability dynamics and outcome of the disease. It is found that if the threshold parameter is less than one the disease free equilibrium is stable and the disease dies out. However, if the threshold parameter is more than one, there exists a unique endemic equilibrium that is locally asymptotically stable. Numerical simulation of the model is also performed by using fourth order Runge - Kutta method. Numerically, it has been found that the system exhibits steady state bifurcation for some parameter values. It is concluded from our analysis that public health education is more efficient if the susceptible individuals are educated in time and followed up by treatment in the exposed subpopulation.
Keywords: HIV/AIDS